PENGARUH SMARTPHONE PADA REMAJA DI SD KARYA BHAKTI HELVETIA MEDAN DITINJAU DARI PERSPEKTIF ISLAM - Rachmat Mico (JURNAL SYIAR-SYIAR, 2022)
A smartphone is a mobile phone that provides features that are above and beyond the simple ability to make phone calls. The various conveniences and sophistication offered by this technology make its users, especially teenagers, dependent. Smartphones have many benefits if used in the right way. However, the use of smartphones by teenagers cannot be separated from positive and negative impacts, even on adolescent morals. The formulation of the problem in this study is the influence of Smartphones on adolescent morals and parents' solutions to the use of Smartphones on adolescent morals at Karya Bhakti Helvetia Elementary School Medan. The purpose of this study was to determine the positive and negative impacts of smartphone use on adolescent morals and parental solutions to these impacts. This research is an explanatory research with a quantitative approach using observation, questionnaire and documentation techniques. The results show that the use of Smartphones has more negative impacts on adolescent morals. The negative impacts are: Time consuming, declining morals and morals of adolescents, declining youth religion and reduced obedience and morals to parents. However, from this, there is a role for parents in providing solutions for smartphone use, including: Providing guidance, supervising children in using smartphones, limiting smartphone use and reminding them to worship.